2020
DOI: 10.1002/mar.21440
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally framed eWOM messages of different valence: The role of environmental concerns, moral norms, and product environmental impact

Abstract: Consumers are increasingly interested to know about the environmental impact (EI) of products and, at the same time, they form attitudes after reading online consumer reviews. Drawing on negativity bias, schema congruity theory, and norm‐activation model, we investigate the effects of environmentally framed electronic word‐of‐mouth messages of different valence, on perceived review usefulness, product attitude and purchase intention in products with low versus high EI. Two factorial experiments (positive vs. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 97 publications
(230 reference statements)
3
27
0
1
Order By: Relevance
“…The moderating role of personal norm has also been found in the context of environmentally framed eWOM messages [22]. In this study, negative reviews of a high environmental impact product vs. negative reviews of a low environmental impact product were perceived to be more useful by consumers with high personal norms, and consumers with low personal norms did not show significant responses [22]. The negative reviews perceived by high personal norm consumers, in turn, negatively impacted attitude and purchase intention.…”
Section: Of 17mentioning
confidence: 53%
See 1 more Smart Citation
“…The moderating role of personal norm has also been found in the context of environmentally framed eWOM messages [22]. In this study, negative reviews of a high environmental impact product vs. negative reviews of a low environmental impact product were perceived to be more useful by consumers with high personal norms, and consumers with low personal norms did not show significant responses [22]. The negative reviews perceived by high personal norm consumers, in turn, negatively impacted attitude and purchase intention.…”
Section: Of 17mentioning
confidence: 53%
“…It was revealed that personal norms play a moderating role in compliance with proenvironmental social norms, and the activation of personal norms can fill the void of social norm receptiveness [21]. The moderating role of personal norm has also been found in the context of environmentally framed eWOM messages [22]. In this study, negative reviews of a high environmental impact product vs. negative reviews of a low environmental impact product were perceived to be more useful by consumers with high personal norms, and consumers with low personal norms did not show significant responses [22].…”
Section: Of 17mentioning
confidence: 89%
“…Beyond the inherently moral (or immoral) aspects of marketing and consumption, associating products with moral philosophies or ideologies can affect consumer perceptions of specific products and brand evaluations (Carrington et al, 2015; Henry, 2010; Lafferty et al, 2004; Newman & Trump, 2017; Singh et al, 2012). When brands clash with consumer attitudes, consumers may evaluate them more adversely (Amar et al, 2018; Filieri et al, 2021; Gvili & Levy, 2021). Conversely, engaging in actions consumers morally support may improve attitudes toward the brand or elicit more brand fidelity (Lafferty et al, 2004; Newman & Trump, 2017).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Beyond their impact on product choice and evaluation, perceived moral violations by companies can lead to adverse downstream effects such as undesirable or negative word of mouth (Filieri et al, 2021; Grappi et al, 2013; Levy et al, 2021; Wetzer et al, 2007; Xie & Bagozzi, 2019). They may even prompt more extreme customer responses, including consumer activism such as protests (Grappi et al, 2013; Hawkins, 2010; Hershkovitz, 2017; Hilton, 2009; John & Klein, 2003; Kozinets & Handelman, 2004; Xie & Bagozzi, 2019), and boycotting (Kozinets & Handelman, 2004).…”
Section: Conceptual Background and Hypothesis Developmentmentioning
confidence: 99%
“…Although the valence (and influence) of UGC in and on review helpfulness, consumer attitude, and behavior show diverging results (cf. Filieri et al, 2021), Sparks and Browning (2011) note that the willingness to book online is higher when (hotel) reviews are predominantly positive (Del Chiappa et al, 2015;Tsao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%